Response of cowpea to sowing date and maize plant population in a Sudan savannah environment - Ewansiha, S.U.; Kamara, A.; Chiezey, U.F.; Onyibe, J.E. (2015)
Maize cultivation has recently expanded to the West African Sudan savannah and has the potential to play a key role in the cropping systems of the region where intercrop yields have been low. Staggering planting date and manipulating plant population of component crops are potential ways to improve yields of intercrops. A field trial was conducted to investigate the performance of contrasting cowpea cultivars when sown at different dates under varying maize plant populations at Minijibir in the Sudan savannah of Nigeria in 2008 and 2009. The trial was laid out in a randomized complete block design with split-split-plot arrangement and replicated four times. Planting date (four and six weeks after sowing maize) formed the main plot; plant population (0, 17,777, 26,666 and 53,333 plants ha-1 ) was assigned to subplots and cowpea cultivars to sub-sub-plots. Results showed that the best grain yield potential for intercropped cowpea was achieved by sowing early in low to moderate maize plant populations. Early sowing was more conducive to achieving a higher number of branches, higher number of peduncles, higher number of pods, and higher fodder and grain yields. Cowpea performance reduced progressively with increase in maize plant population because of increased shading from maize plants. Growing cowpea under high maize population was more favourable for indeterminate cowpea cultivar whereas, growing under zero to moderate maize populations favoured semi-determinate cowpea cultivar most in grain production. Thus, when planning to grow cowpea with maize at full maize crop, farmers may need to seed indeterminate cowpea cultivar early under maize. At reduced maize plant populations, growing maize with semi-determinate cowpea cultivar will do. However, choice of maize plant population to use may depend on the income, food nutrition and feed needs of the farmer.